Image encryption scheme based on a novel fractional order compound chaotic attractor. (30th April 2020) - Zhao, Jian-Feng; Wang, Shu-Ying; Zhang, Li-Tao; Li, Xian-Feng
Many image encryption algorithms have too small key space to prevent exhaust attacks. Based on a novel compound chaotic system, an algorithm with expanded key space is proposed to aim at the problem. Firstly, an adaptive method is provided to design switching controllers during creating a novel compound chaos. Secondly, general Arnold transform is used to realise pixel scrambling technology. Finally, the novel fractional compound chaos is applied in pixel diffusion to improve security of the image encryption algorithm. In numerical simulation, classical colour image, gray image, binary image and non-square image are encrypted sufficiently to identify the encryption algorithm. Both theoretical analysis and experimental results show that the algorithm has larger key space and is suitable for different types of digital images, and encryption image can resist some kinds of external attacks.